Subtalar joint pronation: Which is the real concern-presence or severity? A cross-sectional study - Yahya Süleyman Mollaibrahimoğlu; Nurefşan Kaygas; Özlem Feyzioğlu; Pelin Pişirici (Turkish Journal of Kinesiology)
The study aims to compare static and dynamic postural stability, navicular drop, dorsiflexion range of motion, and jumping performance of individuals with neutral, prone, and hyperprone foot postures. Forty-eight participants between the ages of 18 and 40, were categorized into neutral (n=16), prone (n=16), and hyperprone (n=16) according to foot posture index (FPI). Static and dynamic postural control evaluations (with the Biodex Balance System SD), navicular drop test (NDT) weight-bearing lunge test, countermovement jump test without arm swing, and drop vertical jump tests have been completed. In the results, the average age of participants in the NG, PG, and HPG are 22.31 ± 2.75, 23.87± 3.72, and 22.37 ± 1.28 years and BMI are 22.6 ± 3, 23.4 ± 3.8, and 21.4 ± 2.24 (kg/m²), respectively. The demographic data of the participants showed a homogeneous distribution. There were no significant differences in none of the outcomes except the NDT. Navicular drop amount is positively correlated by the subtalar joint pronation. An increase in subtalar joint pronation does not have a significant effect on static and dynamic stability, jump performance, or dorsiflexion range of motion in healthy individuals.